2012
DOI: 10.1371/journal.pone.0037697
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Regulates Follistatin Function in Ovarian Cancer and Human Ovarian Surface Epithelial Cells

Abstract: Follistatin (FST), a folliculogenesis regulating protein, is found in relatively high concentrations in female ovarian tissues. FST acts as an antagonist to Activin, which is often elevated in human ovarian carcinoma, and thus may serve as a potential target for therapeutic intervention against ovarian cancer. The breast cancer susceptibility gene 1 (BRCA1) is a known tumor suppressor gene in human breast cancer; however its role in ovarian cancer is not well understood. We performed microarray analysis on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…In agreement with our results, it has been shown that FST promotes the proliferation of duck primary myoblasts [45]. The knock-down of FST significantly reduced the proliferation of the immortalized ovarian surface epithelial and human ovarian carcinoma cell line SKOV3 [46]. Previous studies showed STAT3 overexpression inhibited the proliferation of mouse leukocyte and hepatocyte via inhibiting cyclin D expression [38,39], as well as chondrogenic cell line ATDC5 [40].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, it has been shown that FST promotes the proliferation of duck primary myoblasts [45]. The knock-down of FST significantly reduced the proliferation of the immortalized ovarian surface epithelial and human ovarian carcinoma cell line SKOV3 [46]. Previous studies showed STAT3 overexpression inhibited the proliferation of mouse leukocyte and hepatocyte via inhibiting cyclin D expression [38,39], as well as chondrogenic cell line ATDC5 [40].…”
Section: Discussionsupporting
confidence: 92%
“…Additional data suggest that mutations more commonly associated with distinct ovarian cancer histologies including BRCA1 (serous), ARID1A (endometriosis associated clear cell and endometrioid), and FOXL2 (granulosa cell) may promote dysregulation in activin signaling and may further enhance dependence on this pathway (16,17). For example, downregulation of BRCA1 indirectly enhances activin signaling through downregulation of the activin antagonist follistatin alongside upregulation of ActR2B, with the net effect of establishing an autocrine loop feeding cell proliferation (16). Moreover, the tumor suppressor activity of ARID1A is mediated through SMAD3, a key transducer of activin signaling (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Granulosa cell tumours showed enrichment of antagonism of Activin and Follistatin in the Indian Cohort. Follistatin antagonises activin, which is overexpressed in OVCa, with its levels in turn regulated by BRCA1 ( Karve et al, 2012 ). Activin inhibitor STM 434 is in Phase I clinical trial for granulosa cell tumour ( Tao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%